The impact of historical racism on modern gun violence: Redlining in the city of Louisville, KY. Issue 10 (October 2020) - Benns, Matthew; Ruther, Matthew; Nash, Nicholas; Bozeman, Matthew; Harbrecht, Brian; Miller, Keith
Highlights: Modern firearm violence in the united states disproportionately affects african americans and those of low socio-economic status. Redlining refers to the historical practice of the denial of credit based on the location of property within a minority or disadvantaged neighborhood. The most prominent codification of redlining can be seen in maps created for the majority of major cities in the united states during the 1930s. There is a higher incidence of modern gun violence in areas of historical redlining within the city of Louisville, KY. Abstract: Background: The Home Owner's Loan Corporation (HOLC) was created in 1933 to provide government backing of troubled mortgages during the Great Depression. Residential security maps were created to guide investment in over 200 US cities. Neighborhoods were assigned grades of 'A' through 'D' (with corresponding color coding of green, blue, yellow and red) to indicate desirability for investment. Neighborhoods with a high percentage of African Americans or other minorities were frequently assigned grades of 'C' or 'D'. These maps are now most associated with redlining, or the process of denial of credit for real estate investment based on race. Resulting economic disparities endure in areas of many US cities today. We hypothesized that there would be a correlation between redlined areas on the 1937 map of Louisville, KY to the prevalence of gun violence today. Methods: Gunshot victims (GSV) and their residential addresses within the city of Louisville were examined between 2012 and 2018. GSVs were aggregated within census block groups to approximate neighborhoods. The spatial distribution of GSVs was analyzed against the original HOLC neighborhood grade. Additional control variables adapted from the 2013–2017 American Community Survey were included to account for other possible explanations for the spatial distribution of GSVs. A zero-inflated negative binomial regression with a spatial component was used to determine incidence rate ratios (IRR) for the relative likelihood of GSVs within neighborhoods. Results: Relative to green-graded neighborhoods, red-graded neighborhoods had five times as many GSVs. This difference remained statistically significant after accounting for differences in demographic, racial, and housing characteristics of the neighborhoods. Conclusion: Redlined neighborhoods within Louisville, KY in 1937 had significantly more GSVs today. The impact of historical and institutional racism on modern gun violence merits acknowledgement and further study.